Is epileptiform activity related to developmental language disorder? Findings from the HelSLI study - Hanna-Reetta Lajunen; Marja Laasonen; Pekka Lahti-Nuuttila; Miika Leminen; Sini Smolander; Sari Kunnari; Eva Arkkila; Leena Lauronen (Clinical Neurophysiology Practice, 2023)
Objective: To study if interictal epileptiform discharges (IEDs) are associated with language performance or pre-/perinatal factors in children with developmental language disorder (DLD). Methods: We recorded routine EEG in wake and sleep in 205 children aged 2.9–7.1 years with DLD, without neurologic diseases or intellectual disability. We examined the language performance of the children and collected data on pre-/perinatal factors. Results: Interictal epileptiform discharges were not associated with lower language performance. Children with so-called “rolandic”, i.e. centrotemporoparietal, IEDs had better language skills, but age explained this association. Most pre-/perinatal factors evaluated did not increase the risk of rolandic IEDs, except for maternal smoking (OR 4.4, 95% CI 1.4–14). We did not find electrical status epilepticus during slow-wave sleep (ESES)/spike-and-wave activation in sleep (SWAS) in any children. Conclusions: Interictal epileptiform discharges are not associated with lower language performance, and ESES/SWAS is not common in children with DLD. Significance: Routine EEGs do not bring additional information about language performance in children with DLD who do not have any neurologic diseases, seizures, intellectual disability, or regression of language development.